Holly and Nick hate Christmas : a novel - St. Amant, Betsy (WaterBrook, 2025)
"When a Christmas-hating woman's brother sets her up with a fellow Grinch and it backfires, she decides to out-Christmas her date by setting up a festive battle wills in this enemies-to-lovers holiday romcom"--